Pengaruh Metode Mc Kenzie Exercise dan Core Stability Exercise terhadap Penurunan Nyeri pada Penderita Hernia Nucleus Pulposus - Redi Tantangan; Siti Sarah Bintang; Samuel Ginting (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2021)
Hernia Nucleus Pulposus (HNP) is one of the causes of lower back pain due to heavy mechanical loads for a long time. HNP if not treated immediately it can cause fluid buildup and swelling that can cause permanent nerve damage. This study is a quantitative study with a quasi-experimental pre-test-post-test design with a control group divided into 3 groups. The sampling technique was using probability sampling method as many as 30 respondents who visited Grandmed Lubuk Pakam Hospital. The results of the statistical test showed that there was an effect of McKenzie and Core Stability Exercise on reducing pain in patients with HNP with a p value of 0.020 <0.05.